Supervision, control, and data acquisition system of a heat exchanger - Martín Díaz-Choque; Vidalina Chaccara-Contreras; Giorgio Aquije-Cárdenas; Raquel Atoche-Wong; Victor Villanueva-Acosta; Carlos Gamarra-Bustillos; Oscar Samanamud-Loyola (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Today, when industry 4.0 is already being talked about, and its advantages at the organizational level, there are still industrial processes that show a lack of automatic regulation mechanisms, which means that an optimal operating process is not guaranteed, nor that monitoring and supervision capacity. In this sense, the purpose of the article is to demonstrate the feasibility of the integration between the programmable logic controller and the Arduino nanocontrollers, this as an alternative to automate a concentric tube heat exchanger, for monitoring and data acquisition through a supervision, control and data acquisition system. The integration is shown through the design and implementation of a temperature transducer made up of a MAX6675 converter module and an Arduino Nano controller, which is amplified through its pulse width modulation (PWM) interface and the integrated TL081CP and coupled to the analog inputs of the automaton. As a result of the experimental tests, it was possible to determine that the flow rate of the automated system is directly proportional to the drop or difference in temperature in the hot fluid and inversely proportional to the increase in temperature in the cold fluid, verifying the effectiveness of the automated heat exchanger.